A Novel and Advanced Diagnostic Approach toward Paracidovorax citrulli Causing Bacterial Fruit Blotch in Watermelon by Direct SYBR Green Real-Time PCR Assay - Hyeonheui Ham; Bang Wool Lee; Kyongnim Kim; Woohyung Lee; Yong Hwan Lee; Dong Suk Park (The Plant Pathology Journal)
Bacterial fruit blotch (BFB) caused by Paracidovorax citrulli is a devastating disease in cucurbit hosts such as watermelon. P. citrulli is a seed-borne pathogen, and contaminated seeds are the primary inoculum. Because it is difficult to control BFB after the emergence of the disease, it is essential to detect the pathogen and remove infected plant materials, including seeds, in the early stages. In this study, we developed a direct SYBR Green real-time polymerase chain reaction (PCR) method using a new species-specific marker for detecting P. citrulli with high specificity and sensitivity. The genome information of P. citrulli and related species was collected and compared to retrieve the P. citrulli-specific gene. The primer set RS01560-164 was designed based on the selected gene and tested for specificity and sensitivity using cloned DNA, genomic DNA, cell suspension, and suspensions obtained from infected watermelon cotyledons. Our primer set detected only P. citrulli from the closely related species with a detection limit of cloned DNA at 1.46 × 103 copies/μl, gDNA at 500 fg/μl, and cell suspension at 1.4 × 104 cfu/ml by real-time PCR. Our method also detected P. citrulli from diseased plants without the need for a DNA extraction phase. Therefore, the primer set and real-time PCR methods newly developed in this study could be applied for the specific detection of P. citrulli in plants or seeds with high sensitivity and robustness, providing the potential to manage BFB in cucurbits.